2010
DOI: 10.1111/j.1745-4565.2010.00238.x
|View full text |Cite
|
Sign up to set email alerts
|

INHIBITION OF LISTERIA MONOCYTOGENES AND ESCHERICHIA COLI O157:H7 ON FRANKFURTERS USING SCALLOP‐SHELL POWDER

Abstract: This study investigated the effect of scallop‐shell powder (SSP) on the growth of Listeria monocytogenes or Escherichia coli O157:H7 on frankfurters. The frankfurters inoculated with L. monocytogenes or E. coli O157:H7 were immersed in a 0, 0.05 or 0.1% (w/v) SSP slurry for 10 or 30 min. Populations of L. monocytogenes, E. coli O157:H7, mesophilic aerobic bacteria (MAB), lactic acid bacteria and yeast/mold were determined at 0 or 7th days of storage at 4C along the level of L‐ascorbic acid, moisture content, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 16 publications
5
17
0
Order By: Relevance
“…3b). Similar to our results, Bodur et al (2010) also reported that initial populations of E. coli O157:H7 on frankfurters (9.2 logs CFU/g) decreased by 5.0 or 5.9 log CFU/g following 10 min exposures to a 0.05 or 0.10% SSP slurry, respectively. Previous studies have also shown that shell powder could inhibit E. coli in laboratory media (Sawai et al, 1997; with Bae et al (2006) reporting a decrease of 2.78 logs CFU/mL (99%) after a 10 min treatment to 0.05% CaO.…”
Section: Escherichia Coli O157:h7supporting
confidence: 93%
See 2 more Smart Citations
“…3b). Similar to our results, Bodur et al (2010) also reported that initial populations of E. coli O157:H7 on frankfurters (9.2 logs CFU/g) decreased by 5.0 or 5.9 log CFU/g following 10 min exposures to a 0.05 or 0.10% SSP slurry, respectively. Previous studies have also shown that shell powder could inhibit E. coli in laboratory media (Sawai et al, 1997; with Bae et al (2006) reporting a decrease of 2.78 logs CFU/mL (99%) after a 10 min treatment to 0.05% CaO.…”
Section: Escherichia Coli O157:h7supporting
confidence: 93%
“…1b). Similarly, Cagri-Mehmetoglu & Yaldirak (2009) and Bodur et al (2010) also found that a 0.1 or 0.5% SSP slurry reduced the number of L. monocytogenes cells on frankfurters and chicken skins by 3.6 or 3.7 log 10 CFU/g, respectively. Bae et al (2006) also reported that L. monocytogenes populations decreased 1.4 logs following a 10 min exposure to 0.05% CaO.…”
Section: Monocytogenesmentioning
confidence: 88%
See 1 more Smart Citation
“…The heat-transferred samples showed inhibitory activity to all tested bacteria, which is similar to results of other studies [25,26]. For example, calcined scallop shell powder inhibited L. monocytes and E. coli growth and reduced the total number of aerobic mesophilic bacteria in processed sausage without affecting the product texture [27]. In the present study, all samples were further examined using the MPN method.…”
Section: Discussionsupporting
confidence: 64%
“…HSSP is classified as an existing food additive to fortify calcium in the Food Sanitation Law in Japan. Thus, the use of HSSP in food processing is expected to provide a source of minerals, as well as prolong the shelf-life of foodstuffs (Bodur et al, 2010;Kim et al, 2011;Mehmetoglu, 2011;Sawai et al, 2001b) and reduce the pollution caused by scallop shell waste. Sodium hypochlorite at an available chlorine concentration of 50 − 200 ppm is widely used for the disinfection of fresh vegetables and preparation equipment.…”
Section: Resultsmentioning
confidence: 99%